Manuscript (Fath al-Majid fi Qawa'id al-Tajwid) by the scholar Sheikh Ma'ruf al-Nawdhi Study and Verification - Abdullah., Dr.Aram Jalal; Ahmed, Dr. Saadoun Hussein (Sulaimani Journal for Humanities, 2024)
This research is a study and investigation of a manuscript on the science of Tajweed, entitled (Fath al-Majid fi Qawa’id al-Tajweed) - in Persian - by the scholar Sheikh Ma’ruf al-Nawdahi (d. 1254 AH - 1838 AD), who contributed much to the library of Qur’anic studies, including a poem on the science of Tajweed called (al-Jawhar al-Nadid fi ‘Ilm al-Tajweed), which is printed within the complete works of al-Nawdahi. In this manuscript that we are investigating, al-Nawdahi addressed the most important issues of the science of Tajweed briefly, with reference to the opinions of some scholars of Tajweed, in order to enrich students of Tajweed and the serious reader of the Holy Qur’an with what makes them independent of books that are far from their reach. All of this prompted us to investigate it, as well as to revive al-Nawdahi’s effort and his wonderful masterpiece that does not deserve to be forgotten and neglected in the library of manuscripts, and to highlight the efforts of Kurdish scholars in enriching the Qur’anic library.
Keywords: Sheikh Maarouf AlNoudhi; manuscript (Fath AlMajid fi Qawaid AlTajweed); the science of Tajweed; description of the manuscript copies